LOCUTION AND PERLOCUTION IN ENGLISH TEACHERS AND STUDENTS’ CLASSROOM INTERACTION - Yoel Wibowo (Widya Mandala Surabaya Catholic University, 2017)
This research was intended to provide an analysis on English teacher’s locution influence towards students’ perlocution in an Indonesian EFL classroom as well as an elaboration towards the aspects influencing it. This research observed the flow between teachers’ locution and students’ perlocution within two different secondary grade EFL classes by analyzing the transcription of verbal recordings taken during a classroom interaction. This research revealed that the teacher-students verbal interaction within the EFL classroom sample, may be assessed through the students’ response; the use of English as the target language; the quantity of maxim disorders; the use of triggering questions, fillers, confirmation requests, and the rhetorical questions used by the students. On the other hand, aspects considered to be influential to build the students’ perlocution upon the teachers’ locution covered the teachers’ physical appearance and grooming, respect from the students, teaching method, ability to handle the class, relationship with the students, teaching style, voice quality, consistency in using English as the target language inside the classroom, and willingness to assist.